Composition and evolution of volcanic aerosol from eruptions of Kasatochi, Sarychev and Eyjafjallajökull in 2008-2010 based on CARIBIC observations - Andersson, S. M.; Martinsson, B. G.; Friberg, J.; Brenninkmeijer, C. A. M.; Rauthe-Schöch, A.; Hermann, M.; Velthoven, P. F. J. van; Zahn, A. (European Geosciences Union, 2014)
Large volcanic eruptions impact significantly on climate and lead to ozone depletion due to injection of particles and gases into the stratosphere where their residence times are long. In this the composition of volcanic aerosol is an important but inadequately studied factor. Samples of volcanically influenced aerosol were collected following the Kasatochi (Alaska), Sarychev (Russia) and also during the Eyjafjallajökull (Iceland) eruptions in the period 2008–2010. Sampling was conducted by the CARIBIC platform during regular flights at an altitude of 10–12 km as well as during dedicated flights through the volcanic clouds from the eruption of Eyjafjallajökull in spring 2010. Elemental concentrations of the collected aerosol were obtained by acceleratorbased analysis. Aerosol from the Eyjafjallajökull volcanic clouds was identified by high concentrations of sulphur and elements pointing to crustal origin, and confirmed by trajectory analysis. Signatures of volcanic influence were also used to detect volcanic aerosol in stratospheric samples collected following the Sarychev and Kasatochi eruptions. In total it was possible to identify 17 relevant samples collected between 1 and more than 100 days following the eruptions studied. The volcanically influenced aerosol mainly consisted of ash, sulphate and included a carbonaceous component. Samples collected in the volcanic cloud from Eyjafjallajökull were dominated by the ash and sulphate component (~45% each) while samples collected in the tropopause region and LMS mainly consisted of sulphate (50–77 %) and carbon (21–43 %). These fractions were increasing/decreasing with the age of the aerosol. Because of the long observation period, it was possible to analyze the evolution of the relationship between the ash and sulphate components of the volcanic aerosol. From this analysis the residence time (1/e) of sulphur dioxide in the studied volcanic cloud was estimated to be 45±22 days.